Comparative Analysis of Article 21 Income Tax Calculation Using Net, Gross, Gross-Up Methods at the Balai Besar Wilayah Sungai Cimanuk - Cisanggarung - Saputra, Rajib; Hidayat, Firman (Journal of Accounting and Finance Management, 2025)
The Indonesian government depends on taxation as the primary source of revenue for national development.  Article 21 Income Tax (PPh Article 21) directly affects the taxable income of coIDRorations.  This study assesses and contrasts three distinct methodologies for computing Article 21 Income Tax at the Balai Besar Wilayah Sungai (BBWS) Cimanuk - Cisanggarung.  The aim of this research is to identify the most effective strategy for coIDRorate income tax planning.  This study employs a descriptive methodology utilizing a case study approach, augmented by quantitative data gathered through observation, interviews, and documentation.  The research findings indicate that while the Net method yields substantial take-home pay for employees, the institution bears complete responsibility for the obligations of Article 21 Income Tax and cannot receive fiscal support.  The Gross method diminishes employees' net pay as the employer assumes responsibility for the Income Tax Article 21.  The Gross-Up method entails granting employees a tax allowance equivalent to the payable PPh Pasal 21.  The agency can fiscally finance this tax allowance, thereby reducing the coIDRoration's taxable income.  The findings indicate that the Gross-Up method is a superior tax planning strategy for BBWS Cimanuk Cisanggarung.